Adenocarcinoma of the rete testis - a rare case of testicular malignancy - Chovanec, M; Mego, M; Sycova-Mila, Z; Obertova, J; Rajec, J; Palacka, P; Mardiak, J (Klinicka onkologie, 2014)
BACKGROUND: Adenocarcinoma of rete testis is an extremely rare dia-gnosis described in around 70 patients worldwide. The prognosis of the disease in metastatic stage is very poor and there is no standard systemic treatment available. CASE: Herein we present a unique case report of a 47-year- old man with metastatic adenocarcinoma of rete testis who achieved substantial disease response after four cycles of paclitaxel, ifosfamide and cisplatin. The chemotherapy was administered in five -day regimen, which comprised 250 mg/ m2 of paclitaxel on day one, 20 mg/ m2 of cisplatin on day one to five and 1,2 g/ m2 of ifosfamide on day one to five, in a three-week interval. The patient received prophylactic pegfilgrastim after each cycle of TIP. The treatment was well tolerated - without any significant toxicity. RESULT: Patient achieved a partial 14- month remission. CONCLUSION: On basis of this experience we suggest that paclitaxel, ifosfamide and cisplatin might be adopted as novel agents in treatment of rete testis adenocarcinoma.
Keywords: Adenocarcinoma; filgrastim; Humans; ifosfamid; cisplatina; lidé středního věku; Cisplatin; protokoly protinádorové kombinované chemoterapie; testikulární nádory; lidé; Recombinant Proteins; Polyethylene Glycols; Ifosfamide; faktor stimulující kolonie granulocytů; rekombinantní proteiny; Testicular Neoplasms; Rete Testis; rete testis; Male; Middle Aged; paclitaxel; Antineoplastic Combined Chemotherapy Protocols; Filgrastim; Granulocyte Colony-Stimulating Factor; adenokarcinom; Paclitaxel; polyethylenglykoly; mužské pohlaví